2012
DOI: 10.1016/j.jadohealth.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Weighing Behaviors in Young Adults: Tipping the Scale Toward Unhealthy Eating Behaviors?

Abstract: Purpose This study examined associations between frequency of self-weighing and healthy weight control behaviors, unhealthy weight control behaviors, muscle enhancing behaviors (e.g. steroid use, protein powders), and psychological well-being (i.e., self-esteem, depression, body satisfaction) in a community sample of young adults. Methods Data were drawn from Project EAT-III (Eating and Activity in Teens and Young Adults), the third wave of a population-based study. Participants included young adults (n=2,28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 31 publications
11
50
1
Order By: Relevance
“…They concluded that “young adults who monitored their weight a few times per week or more reported significantly more depressive symptoms (in women) and poorer body satisfaction (in men) compared with young adults who monitored their weight less often” (p. 472). While these results appear to contradict previously discussed studies (Gokee-Larose et al, 2009; Wing et al, 2007) and support the original warning by Ogden and Whyman (1997), the results of the Quick et al (2012) study were correlational. It is equally plausible that depressed females or males with poor body satisfaction chose to weigh themselves more frequently than nondepressed, body-satisfied females or males as it is that frequent self-weighing causes depression or poor body satisfaction.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…They concluded that “young adults who monitored their weight a few times per week or more reported significantly more depressive symptoms (in women) and poorer body satisfaction (in men) compared with young adults who monitored their weight less often” (p. 472). While these results appear to contradict previously discussed studies (Gokee-Larose et al, 2009; Wing et al, 2007) and support the original warning by Ogden and Whyman (1997), the results of the Quick et al (2012) study were correlational. It is equally plausible that depressed females or males with poor body satisfaction chose to weigh themselves more frequently than nondepressed, body-satisfied females or males as it is that frequent self-weighing causes depression or poor body satisfaction.…”
Section: Resultscontrasting
confidence: 87%
“…Using food substitutes (meal replacements) is a weight control strategy with strong supporting evidence and was endorsed in position papers of the (former) American Dietetic Association (Fitch & Keim, 2012; Jonnalagadda, Jones, & Black, 2005; Seagle, Strain, Makris, & Reeves, 2009). In addition to finding relationships between weighing and unhealthy weight-control practices, Quick et al (2012) reported positive relationships between weighing and health weight-control practices as well. They concluded that “young adults who monitored their weight a few times per week or more reported significantly more depressive symptoms (in women) and poorer body satisfaction (in men) compared with young adults who monitored their weight less often” (p. 472).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Some research indicates that frequent self-weighing in young adulthood is associated with binge eating and depression [97]—particularly among young women [98]. Within treatment-seeking samples of young adults, however, frequent self-weighing is associated with better weight outcomes [99100] and healthy weight control behaviors [101].…”
Section: Perceptions Of Specific Weight-related Behaviorsmentioning
confidence: 99%